Usulan Penjadwalan Penggantian dan Pemeriksaan Komponen Kritis Mesin Feeder dan Fanblower (Studi Kasus di PT. Petnesia Resindo) - Ivanasari Latib; Carla Olyvia Doaly (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
Many companies do not pay attention to machine maintenance. One of them is PT Petnesia Resindo. The company that have been engaged in platic is still implementing a breakdown maintenance. This proved to disturb the production process. Sothis research is interested in trying to implement preventive maintenance against the proposed machine company, Research begins with the determination of critical machines based on the OEE level. Both engines are feeder and fanblower engine is including a critical engine. The critical components based on the rules